Pesan Tersirat Dalam Lirik Lagu “The A Team” Karya Penyanyi Eheeran: - Nasution, Elza Hasyim; Nugraha, Gentha; Sazali, Hasan (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The study was intended to describe a music video titled